2013
DOI: 10.4097/kjae.2013.64.2.164
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic experience using total intravenous anesthesia in a patient with Isaacs' syndrome -A case report-

Abstract: We report on an anesthetic experience with a 74-year-old female with Isaacs' syndrome, who underwent elective surgery for open rotator cuff repair. Isaacs' syndrome is a rare peripheral motor neuron disorder with clinical manifestations such as involuntary muscle twitching, cramps, mild weakness and increased sweating. To avoid prolonged neuromuscular blockade, the patient was observed with neuromuscular monitoring during total intravenous anesthesia with propofol, remifentanil, and atracurium. No adverse even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Since previous reports have shown an increase in acetylcholine release in these patients and tolerance of dtubocurarine has been demonstrated in vitro, we can predict a tolerance for non-depolarizing muscle relaxants in patients with Isaacs' syndrome [7,8]. Some reports have suggested that general anesthesia in patients with Isaacs' syndrome does not exacerbate neuromuscular disorders such as myotonia and involuntary muscular contraction [9][10][11]. However, respiratory complications caused by respiratory muscle weakness and laryngeal muscle myotonia can result from anesthesia [9][10][11].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Since previous reports have shown an increase in acetylcholine release in these patients and tolerance of dtubocurarine has been demonstrated in vitro, we can predict a tolerance for non-depolarizing muscle relaxants in patients with Isaacs' syndrome [7,8]. Some reports have suggested that general anesthesia in patients with Isaacs' syndrome does not exacerbate neuromuscular disorders such as myotonia and involuntary muscular contraction [9][10][11]. However, respiratory complications caused by respiratory muscle weakness and laryngeal muscle myotonia can result from anesthesia [9][10][11].…”
Section: Discussionmentioning
confidence: 80%
“…Some reports have suggested that general anesthesia in patients with Isaacs' syndrome does not exacerbate neuromuscular disorders such as myotonia and involuntary muscular contraction [9][10][11]. However, respiratory complications caused by respiratory muscle weakness and laryngeal muscle myotonia can result from anesthesia [9][10][11]. Furthermore, patients with Isaacs' syndrome are often comorbid with myasthenia gravis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle cramp, slow relaxation following muscle contraction, and excessive sweating (hyperhidrosis) are the main symptoms of Isaacs' syndrome [3] [6] [9]. Patients almost always develop persistent muscle contraction, which is often worse following exercise myokimia, generalized, and fasciculations are also common [10] [11].…”
Section: Discussionmentioning
confidence: 99%
“…and disagreement was resolved by consensus. This left us with a total of 61 case reports and 4 case series 14,16,30–91 (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%